InGaAs based heterojunction phototransistors: Viable solution for high-speed and low-noise short wave infrared imaging - Rezaei, Mohsen; Park, Min-Su; Rabinowitz, Cobi; Tan, Chee Leong; Wheaton, Skylar; Ulmer, Melville; Mohseni, Hooman (AIP Publishing, 2019)
Highly sensitive and fast imaging at short-wavelength infrared (SWIR) is one of the key enabling technologies for the direct-imaging of habitable exoplanets. SWIR imaging systems currently available in the market are dominated by imagers based on InGaAs PIN photodiodes. The sensitivity of these cameras is limited by their read-out noise (RON) level. Sensors with internal gain can suppress the RON and achieve lower noise imaging. In this paper, we demonstrate a SWIR camera based on 3D-engineered InP/InGaAs heterojunction phototransistors with responsivities around 2000 A/W which provides a shot-noise limited imaging sensitivity at a very low light level. We present the details of the semiconductor structure, the microfabrication, and the heterogeneous integration of this camera. The low capacitance pixels of the imager achieve 36 electron effective RON at frame rates around 5 kilo-frames per second at an operating temperature of 220 K and a bias voltage of 1.1 V. This is a significant step toward achieving highly sensitive imaging at SWIR at high frame rates and noncryogenic operating temperatures. Based on the proposed modeling and experimental results, a clear path to reach the RON less than 10 electrons is presented. © 2019 Author(s).